Teaching Performance from the Students' View: An Instrument to Evaluate Teachers - Pumapillo-Rosas, Milagros (2024)
The aim of the study is to propose an instrument that evaluates the teacher's performance from the perspective of their students which is based on the Good Teaching Performance Framework. The instrument got the evidence of validity and reliability that supported the relevance of the instrument with the assessment of nine experts. In the research, 62 studentsparticipated, distributed in 30 (48%) women and 32 (52%) men in secondary school between the ages from 14 to 17; 35% were in third grade, 37% in fourth grade and 28% in fifth grade of secondary school. The instrument is made up of 40 items focused on the four dimensions of the MBDD. Its validity was evidenced through the Aiken V coefficient that fluctuated between 0.83 and 1 in a 95% confidence interval, having clarity, relevance and coherence. Reliability was analyzed using Cronbach's alpha coefficient, which amounted to 0.92, its relevance being reliable. The results conclude that the teaching performance evaluation instrument is reliable and valid for its application.